A pilot study investigating a novel subcutaneously implanted pre-cellularised scaffold for tissue engineering of intestinal mucosa - D A J Lloyd; T I Ansari; P Gundabolu; S Shurey; V Maquet; P D Sibbons; A R Boccaccini; S M Gabe (European Cells & Materials, 2006)
Tissue engineering of the small intestine offers an alternative to long-term intravenous nutrition and transplantation in patients with intestinal failure. Initial work, although encouraging, is limited by the volume of neonatal tissue required to produce a small neomucosal cyst. Our novel approach is to implant tubular poly-lactide-co-glycolide (PGLA) foam scaffolds subcutaneously. The aim of this study was to investigate whether these scaffolds would support growth of intestinal neomucosa. PGLA scaffolds were implanted subcutaneously into 8 Lewis rats; after 5 weeks, 'organoid units' were injected into the lumens. Tissue was assessed histologically after harvesting and quantitative immunohistochemistry was performed using antibodies against vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 2 (VEGF-R2), fibroblast growth factor basic (bFGF) and fibroblast growth factor receptor 2 (FGF-R2). At 4 weeks post organoid unit implantation, clearly recognisable mucosa and submucosa was present on the luminal surface of the scaffold. Densities of VEGF and VEGF-R2 positive cells increased with time post organoid unit implantation. This pilot study demonstrates that it is possible to tissue engineer small intestinal neomucosa using subcutaneously implanted PLGA scaffolds. The yield of the process compares favourably to the published literature. Further work is required to optimise the technique.